2013
DOI: 10.1177/0021998313482158
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and impact behaviour of carbon/basalt fibers hybrid laminates

Abstract: Basalt and E-glass fibers fabrics were combined with carbon fiber fabrics in order to prepare epoxy-based interlaminar hybrid composites and to investigate the hybridization effect on the flexural and impact properties of the resulting laminates. The flexural modulus of the composites depended on their composition according to a rule of mixture, while an important synergistic effect was detected for the ultimate flexural properties. Charpy impact tests evidenced a strength increase as basalt and glass fibers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 46 publications
3
38
0
1
Order By: Relevance
“…carbon/E glass fibre fabrics [19], carbon/basalt fibre fabrics [19], glass/Kevlar fabrics [20] and carbon/basalt fibres [21]. Some studies showed potential existence of hybrid effects.…”
Section: Introductionmentioning
confidence: 99%
“…carbon/E glass fibre fabrics [19], carbon/basalt fibre fabrics [19], glass/Kevlar fabrics [20] and carbon/basalt fibres [21]. Some studies showed potential existence of hybrid effects.…”
Section: Introductionmentioning
confidence: 99%
“…Petrucci et al [8] examined the impact and flexural postimpact behavior of ternary hybrid composites based on epoxy resin reinforced with basalt, flex, hemp and glass fibres. Dorigato and Pegoretti [9] investigated the hybridization effect on the flexural and impact properties of carbon/basalt fibre reinforced composite laminates. All these studies have reported the tensile, compressive, flexural, impact and thermal properties of basalt fiber reinforced composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Because, winding tension has shown more pronounced effect on trapezoid corners, the excess amount of resin has been removed from the structure, which resulted in a signifi cant decrease of resin's weight percent on the corners. Voids formation and infl uence in composite structures has been reported in (Huber, 1996;Risteska et al, 2014;Dorigato and Pegoretti, 2014). Also, voids were detected in the cross section of the hybrid structure sides (Fig.…”
Section: Resultsmentioning
confidence: 55%